Analisis Pengetahuan, Motivasi, Keterampilan Tenaga Kesehatan Terhadap Pelaporan Insiden Keselamatan Pasien di Puskesmas Kabupaten Kotawaringin Barat - Afriyani, Nur; Indasah, Indasah; Suhita, Byba Melda (Civiliza Publishing, 2025)
This study analyzes the influence of knowledge, motivation, and skills of health workers on the reporting of patient safety incidents at the West Kotawaringin Regency Health Center. This study uses an observational design with a cross-sectional approach. The research sample consisted of 116 health workers who were randomly selected in six health centers in West Kotawaringin Regency. The independent variables in this study were knowledge, motivation, and skills, while the dependent variable was patient safety incident reporting. Data were collected using questionnaires that had been tested for validity and reliability, then analyzed using binary logistic regression. The results showed that knowledge (p=0.001), motivation (p=0.002), and skills (p=0.000) significantly affected patient safety incident reporting. Simultaneously, these three variables contributed 56% to patient safety incident reporting. Good knowledge increases understanding of the importance of reporting, high motivation encourages reporting consistency, and adequate skills ensure reporting is done correctly and efficiently. The conclusion of this study confirms the importance of improving the knowledge, motivation, and skills of health workers in supporting patient safety incident reporting systems. As a recommendation, Puskesmas are advised to organize continuous training that includes aspects of knowledge, motivation, and skills, as well as providing incentives to increase the motivation of health workers. The implementation of this strategy is expected to improve the quality of incident reporting and improve patient safety.